STUDY OF CLINICAL AND PARACLINICAL CHARACTERISTICS AND MODE OF DELIVERY IN CASES OF NUCHAL CORD (Vietnam Journal of Community Medicine, 2026)
Objectives: This study investigates the clinical and paraclinical characteristics and methods of pregnancy termination in cases of nuchal cord entanglement.Subjects and methods: Descriptive cross-sectional study. Pregnant women meeting the criteria in the study sample.Results: The average age of the study group was 27.75 ± 6.78 years, ranging from 18 to 44 years. The majority lived in urban areas with 72.37%, while 27.63% lived in rural areas. There were 42.5% with umbilical cord entanglement around the neck. 82.3% had umbilical cord entanglement once, and 7.5% had umbilical cord entanglement twice. The average umbilical cord length in the study was 50.40 ± 3.53 cm, with the shortest 40 cm and the longest 58 cm. Obstetric monitoring in group 1 accounted for a high percentage (95%). The rate of cesarean section in the study group was higher than in the vaginal delivery group (51.25% vs. 48.75%). For umbilical cord entanglement once, the rate of vaginal delivery was higher than that of cesarean section. In cases where the umbilical cord is wrapped around the neck twice, the cesarean section rate is higher.Conclusion: A high frequency of nuchal cord was observed in the study population.
Keywords: Cesarean section, nuchal cord, umbilical cord length